A new species of lowland skink (genus Lipinia Gray, 1845) from northeastern Peninsular Malaysia - Grismer, L. Lee; Ismail, Lukman H.b.; Awang, Muhammad Taufik; Rizal, Syed A.; Ahmad, Amirrudin B. (Zootaxa, 2014)
A new species of scincid lizard, Lipinia sekayuensis sp. nov. from Hutan Lipur Sekayu, Terengganu State in northeastern Peninsular Malaysia is most similar to L. surda (Boulenger) but differentiated from it and all other species of Lipinia by having the combination of an adult SVL of 42.3 mm; six supralabials; five infralabials; four supraoculars; prefrontals widely separated; two loreals; fused frontoparietals; lower eyelids bearing a large, transparent disc; 21 midbody scale rows; 56 paravertertebral scale rows; 65 ventral scale rows; enlarged, precloacal scales; 10 subdigital lamellae on the third finger; 11, 15, and seven lamellae on the third, fourth, and fifth toes, respectively; distal subdigital lamellae keeled; a median row of slightly enlarged, subcaudal scales present; a generally unicolor, dark-brown dorsum bearing nine very faint, diffuse, darker stripes; and an external ear opening replaced by a scaly, auditory depression.